WASP-69b’s Escaping Envelope Is Confined to a Tail Extending at Least 7 Rp - Dakotah Tyler; Erik A. Petigura; Antonija Oklopčić; Trevor J. David (The Astrophysical Journal, 2024)
Studying the escaping atmospheres of highly irradiated exoplanets is critical for understanding the physical mechanisms that shape the demographics of close-in planets. A number of planetary outflows have been observed as excess H/He absorption during/after transit. Such an outflow has been observed for WASP-69b by multiple groups that disagree on the geometry and velocity structure of the outflow. Here, we report the detection of this planet’s outflow using Keck/NIRSPEC for the first time. We observed the outflow 1.28 hr after egress until the target set, demonstrating the outflow extends at least 5.8 × 10 ^5 km or 7.5 R _p This detection is significantly longer than previous observations, which report an outflow extending ∼2.2 planet radii just 1 yr prior. The outflow is blueshifted by −23 km s ^−1 in the planetary rest frame. We estimate a current mass-loss rate of 1 M _⊕ Gyr ^−1 . Our observations are most consistent with an outflow that is strongly sculpted by ram pressure from the stellar wind. However, potential variability in the outflow could be due to time-varying interactions with the stellar wind or differences in instrumental precision.